Association of serum 25(OH)D3 and cognitive levels with biological aging in the elderly: a cross-sectional study - Li, Mingkai; Li, Chenyang; Cheng, Le; Lv, Chenhui; Xue, Lushan; Zhang, Cheng; Bai, Ziping; Wang, Xi; Chen, Shuangzhi; Guo, Qinfei; Zhao, Yafei; Zhao, Haifeng (Frontiers in Nutrition, 2025)
BackgroundBiological aging, a fundamental process affecting health and longevity, is pivotal to understanding the physiological decline associated with aging. Serum vitamin D3 deficiency and cognitive impairment are common health issues among older adults. However, the joint associations of serum vitamin D levels and cognitive impairment with biological aging remain poorly understood. This study aims to evaluate the independent and combined associations of serum vitamin D3 and cognitive impairment with biological aging in older adults.MethodsThis cross-sectional study included adults aged 60 years and older from the 2011–2014 National Health and Nutrition Examination Survey (NHANES). Biological aging was measured using Phenotypic Age calculated from biomarkers. Cognitive performance was assessed using the Centre for the Establishment of a Registry for Alzheimer’s Disease (CERAD) test, the Animal Fluency test (AFT), and the Digit Symbol Substitution test (DSST). Multivariable regression and restricted cubic spline models were used to examine the relationships between serum 25(OH)D3 levels, cognitive performance, and biological aging.ResultsAfter adjusting for all covariates, individuals in the highest quartile of cognitive performance had a reduced risk of biological aging compared to those in the lowest quartile (CERAD: OR 0.91; 95% CI, 0.57–1.46; AFT: OR 0.48; 95% CI, 0.29–0.82; DSST: OR 0.43; 95% CI, 0.24–0.77). A U-shaped relationship was observed between serum 25(OH)D3 levels and biological aging. Combined analyses revealed that individuals with both low serum 25(OH)D3 and low cognitive performance had the highest risk of biological aging across all cognitive tests (CERAD: OR 1.43; 95% CI, 1.02–1.98; AFT: OR 1.70; 95% CI, 1.24–2.32; DSST: OR 1.67; 95% CI, 1.22–2.27). Notably, in the DSST, individuals with normal serum 25(OH)D3 levels and normal cognitive performance showed a reduction in Phenotypic Age by 2.40 years (p < 0.01).ConclusionIn older adults, low serum 25(OH)D3 levels combined with low cognitive performance are strongly associated with an increased risk of biological aging.